Drug therapy for pain in amyotrophic lateral sclerosis or motor neuron disease - Brettschneider, Johannes (Cochrane Database Syst Rev, 2013)
BACKGROUND: Amyotrophic lateral sclerosis (ALS), also known as motor neuron disease (MND), is the most common neurodegenerative disorder of the motor system in adults. Pain in ALS is a frequent symptom especially in the later stages of disease and can have a pronounced influence on quality of life and suffering. Treatment of pain therefore should be recognised as an important aspect of palliative care in ALS. This is an update of a review first published in 2008. OBJECTIVES: To systematically review the evidence for the efficacy of drug therapy in relieving pain in ALS. We also aimed to evaluate possible adverse effects associated with the different drugs and their influence on survival and quality of life. SEARCH METHODS: On 2 July 2012, we searched the following databases: the Cochrane Neuromuscular Disease Group Specialized Register (2 July 2012), CENTRAL (2012, Issue 6 in The Cochrane Library), MEDLINE (January 1966 to June 2012), EMBASE (January 1980 to June 2012), CINAHL (January 1982 to June 2012), AMED (January 1985 to June 2012) and LILACS (January 1982 to June 2012). We checked the bibliographies of trials identified and contacted other disease experts to identify further published and unpublished trials. SELECTION CRITERIA: We searched for randomised or quasi‐randomised controlled trials on drug therapy for pain in amyotrophic lateral sclerosis. DATA COLLECTION AND ANALYSIS: We collected data using a specially designed form and analysed them using the Cochrane Review Manager software. MAIN RESULTS: We found no randomised or quasi‐randomised controlled trials on drug therapy for pain in ALS or MND. AUTHORS' CONCLUSIONS: There is no evidence from randomised controlled trials about the management of pain in ALS. Further research on this important aspect of palliative care in ALS is needed. Randomised controlled trials should be initiated to determine the effectiveness of different analgesics for treatment of pain in ALS.